Comparison of Efficacy of Lisinopril and Losartan for Reducing Microalbuminuria Levels in Patients with Type-2 Diabetes Mellitus (Medical Forum Monthly, 2021)
Objective: To compare the efficacy of losartan and lisinopril for reduction of microalbuminuria in patients with type-2 diabetes mellitus.Study Design: Randomized Control Trial studyPlace and Duration of Study: This study was conducted at the Department of Medicine, Bolan Medical Complex Hospital, Quetta, Pakistan from July 2019 to January 2020.Materials and Methods: A total of 110 with diagnosed type II diabetes mellitus and albumin to creatinine ratio 30–300 mcg/mg creatinine in the 1st early morning urine, age 18-75 of both genders were included. Patients with hypersensitivity to ACE inhibitors or Angiotensin Receptor Blocker, CRF, pregnancy and uncontrolled hypertension were excluded. All the patients were randomly divided into two groups by the lottery method. Group A was treated with 100 mg of Losartan potassium for 12 weeks while Group B patients were given 5 mg of Lisinopril for 12 weeks.Results: The mean age of patients in group A was 39.60 ± 10.12 years and in group B was 41.0 ± 8.05 years. Majority of the patients 56 (50.91%) were between 18 to 45 years of age. Out of 110 patients, 47 (42.78%) were males and 63 (57.27%) were females with male to female ratio of 1:1.3. Efficacy of Group A (losartan group) was seen in 48 (87.27%) patients while in Group B (lisinopril group) was seen in 37 (67.27%) patients (p-value = 0.012)Conclusion: This study concluded that efficacy of losartan is higher than lisinopril for reduction of microalbuminuria in patients with type-2 diabetes mellitus.